Pemberian Nafkah Suami kepada Istri Perspektif Hukum Islam dan Hukum Positif - Sandra (Journal Smart Law, 2024)
This research discusses the provision of husbands to wives according to the perspective of Islamic law and positive law and then examines the similarities and differences. This research is library research, namely research carried out using literature, reading and taking notes and processing research materials in the form of books, notes, journals and the internet. The research results explain the position of alimony according to Islamic law, namely that alimony is the husband's priority in meeting the family's primary needs. The legal basis for livelihood is found in the Al-Qur'an, Hadith and Ijma'. The husband's obligation to provide for his wife's needs according to Islamic law is to fulfill household needs in terms of clothing, food and shelter. Positive law explains that living is provided on the basis of rights and obligations that have been fulfilled. The positive legal basis in Law no. 1 of 1974 concerning marriage and the Compilation of Islamic Law. explains the husband's obligation to support his wife, which explains the obligation to provide support both physically and mentally and provide adequate housing for his family and according to their abilities. The similarity in giving a husband a living to his wife according to Islamic law and positive law is that the living is borne by the husband even though the wife has an income. The difference is that according to Islamic law the level of living has been determined and positive law does not explain the level.